Pengembangan Lembar Kerja Siswa (LKS) Berbasis Model Discovery Learning Menggunakan Canva - Agnes Septisa Sintri; Elya Rosalina; Nur Fitriyana (Journal of Elementary School (JOES), 2023)
This study aims to develop Student Worksheets (LKS) based on the discovery learning model using Canva in mathematics learning class V SD Negeri 03 Terawas. The type of development used is the 4D model (four-D model). The data collection technique uses a validation questionnaire for linguists, material experts and teacher and student practicality questionnaires. Based on the results of research and development, several conclusions can be drawn as follows 1) The design of the Discovery Learning-based LKS for fifth grade students of SD Negeri 03 Terawas was designed using three types of letters, namely Book Antiqua, Comic Sans MS, and Jokerman. Discovery Learning-based worksheets are printed like books in general, using A4 paper with a weight of 75 gr. Discovery Learning-based worksheets are accompanied by images that are in accordance with the material in mathematics learning, the sub-theme of the diverse cultures of my nation. The selection of colors with good resolution, bright, and full color motivates students to be enthusiastic in learning activities.2) Development of Student Worksheets (LKS) based on the Discovery Learning model using canva in learning mathematics class V SD Negeri 03 Terawas which is valid and practical. The validity of the LKS is shown through the results of expert validation which includes media experts, linguists, and material experts. Based on the validation results, it is known that the LKS is categorized as good with a validity percentage of 79,00 so that the LKS on the Material Surface area and volume of flat-sided spaces is categorized as valid. The practicality of the LKS is measured through questionnaire results obtained by small group trials involving 9 students and 1 teacher categorized as very good with a percentage of 87,50%. Keywords: LKS, discovery learning